1987
DOI: 10.1128/aem.53.1.27-32.1987
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Dynamics and Kinetics during High-Rate Sulfate Reduction under Anaerobic Conditions

Abstract: The sulfate kinetics in an anaerobic, sulfate-reducing biofilm were investigated with an annular biofilm reactor. Bioflm growth, sulfide production, and kinetic constants (Km and Vmax) for the bacterial sulfate uptake within the biofilm were determined. These parameters were used to model the biofilm kinetics, and the experimental results were in good agreement with the model predictions. Typical zero-order volume rate constants for sulfate reduction in a biofilm without substrate limitation ranged from 56 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
6

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(40 citation statements)
references
References 30 publications
3
30
1
6
Order By: Relevance
“…This value is higher than would be expected if diffusion were the sole factor controlling observed rates but may underestimate the microbial response to temperature if diffusion limitation did affect the rates. Previous studies have indicated the temperature dependence of sulfate reduction is even more pronounced (Qlo 2.9-3.6; Nielsen 1987;Ingvorsen et al 198 1;Jorgensen 1977).…”
Section: Resultsmentioning
confidence: 94%
“…This value is higher than would be expected if diffusion were the sole factor controlling observed rates but may underestimate the microbial response to temperature if diffusion limitation did affect the rates. Previous studies have indicated the temperature dependence of sulfate reduction is even more pronounced (Qlo 2.9-3.6; Nielsen 1987;Ingvorsen et al 198 1;Jorgensen 1977).…”
Section: Resultsmentioning
confidence: 94%
“…The K m value for sulfate of D. desulfuricans attached to particles (8.4-9.0 /~M) was much lower than those of free-living ones. Nielsen [5] also reported a low K m value (1.4/zM) for SRB attached on a biofilm. These low K m values for attached cells may be due to the adsorption of sulfate to the solid surface.…”
Section: Discussionmentioning
confidence: 97%
“…Most sulfate-reducing bacteria (SRB) were shown to be attached to particles larger than 10 /zm in aquatic sediments [1]. Interaction between SRB and solid particles has been studied by several investigators [2][3][4][5][6][7][8]. Some attempts to examine effects on activity of SRB of solid particles such as silica gel, clay and sand under sufficient concentrations of electron donors and sulfate have produced conflicting results including stimulation [4,5] and inhibition [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that the ground water in the vicinity of this well behaved according to closed system conditions during the monitoring period, which is considered to be a conservative assumption (i.e., there was no additional input of sulfate), the well 2 data indicate an overall bacterial sulfate reduction rate of approximately 1540 mg/L over 21 months (1999 to 2001), equivalent to 2.4 mg/L/d. It is likely that the rate of sulfate reduction at well 2 became diffusion limited once the sulfate was depleted to low levels ( Figure 3) (Nielsen 1987).…”
Section: Evidence For Bacterial Sulfate Reduction As a Key Teap In Thmentioning
confidence: 99%